Literary rendez-vous with Zdeněk Rotrekl or A few remarks on Jiří Zizler's book The Aristocrat of the Catacombs - Sládek, Ondřej (Bohemica Olomucensia, 2023)
The main topic of the study is a critical consideration of the analytical and interpretative methods used by the literary historian and critic Jiří Zizler in his monograph on the poet Zdeněk Rotrekl - The Aristocrat of the Catacombs. Towards the Life and Work of Zdeněk Rotrekl (2021). The study demonstrates that Zizler's book is the result of the combination of several approaches: the literary-critical, historical, and comparative, as well as the structural, phenomenological, and hermeneutical. One must also add the method of close reading, which Zizler uses to create his interpretive models.
Keywords: Jiří Zizler; Zdeněk Rotrekl; poetics; interpretation; Czech catholic literature.